Microeconomics : a programmed book - Lumsden, Keith G. 4 0 16; 1915-1994, Attiyeh, Richard,;Bach, George Leland; 5 (Englewood Cliffs, N.J : Prentice-Hall, 1966)
This is a programmed text. As such it may be used in a number of ways to increase the efficiency with which students can be taught economics. If used by itself at the beginning of a course this text is sufficient to ensure that the reader acquires the rudiments of micro-economic theory and, consequently, can allow the instructor to develop in class more material than would otherwise be possible.
Keywords: 2 -- 0; 6; Economics -- 20 -- Programmed instruction; 20; 2